2017
DOI: 10.1021/acs.est.7b01909
|View full text |Cite
|
Sign up to set email alerts
|

Cross Validation of Two Partitioning-Based Sampling Approaches in Mesocosms Containing PCB Contaminated Field Sediment, Biota, and Activated Carbon Amendment

Abstract: The Gold Standard for determining freely dissolved concentrations (C) of hydrophobic organic compounds in sediment interstitial water would be in situ deployment combined with equilibrium sampling, which is generally difficult to achieve. In the present study, ex situ equilibrium sampling with multiple thicknesses of silicone and in situ pre-equilibrium sampling with low density polyethylene (LDPE) loaded with performance reference compounds were applied independently to measure polychlorinated biphenyls (PCBs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 23 publications
(51 citation statements)
references
References 33 publications
1
50
0
Order By: Relevance
“…However, lower lipid levels were found in amphipods (ANOVA; p < 0.001) exposed to New Bedford Harbor and Gould Island sediments compared with those exposed to control sediment (Supplemental Data, Figure S6). This finding suggests that PCBs and other contaminants (e.g., metals and non-HOCs) in the sediment likely contributed to the observed effect (Naval Facilities Engineering Command 2014;Schmidt et al 2017;US Environmental Protection Agency 2018c). For example, PAHs were recently detected in New Bedford Harbor sediment samples at a total concentration of 10 mg/kg dry weight (Schmidt et al 2017).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, lower lipid levels were found in amphipods (ANOVA; p < 0.001) exposed to New Bedford Harbor and Gould Island sediments compared with those exposed to control sediment (Supplemental Data, Figure S6). This finding suggests that PCBs and other contaminants (e.g., metals and non-HOCs) in the sediment likely contributed to the observed effect (Naval Facilities Engineering Command 2014;Schmidt et al 2017;US Environmental Protection Agency 2018c). For example, PAHs were recently detected in New Bedford Harbor sediment samples at a total concentration of 10 mg/kg dry weight (Schmidt et al 2017).…”
Section: Discussionmentioning
confidence: 96%
“…This finding suggests that PCBs and other contaminants (e.g., metals and non-HOCs) in the sediment likely contributed to the observed effect (Naval Facilities Engineering Command 2014;Schmidt et al 2017;US Environmental Protection Agency 2018c). For example, PAHs were recently detected in New Bedford Harbor sediment samples at a total concentration of 10 mg/kg dry weight (Schmidt et al 2017). Also, nutrients and sewage discharges have been reported in New Bedford's coastal waters (Voyer et al 2000).…”
Section: Discussionmentioning
confidence: 96%
“…Equilibrium sampling using jars coated with multiple thicknesses of silicone has successfully been applied for studying HOCs in soil (Reichenberg et al, 2008;Määenpää et al, 2011), marine (Jahnke et al, 2012;Schmidt et al, 2017), lake (Jahnke et al, 2014), and river sediments (Schäfer et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Uncertainty in C free can arise from either the K PEW estimates used or from the CPE value measured or calculated from the deployment. Cross‐validation experiments have shown that C free values derived using different passive sampling mediums like silicone rubber, semipermeable membrane devices, and polyethylene often perform similarly and yield C free estimates that are within a factor of 2 (Fernandez et al 2012; Jacquet et al 2014; Schmidt et al 2017). These studies provide confidence in the partitioning coefficients ( K PEW ) that are available for polyethylene.…”
Section: Introductionmentioning
confidence: 99%
“…Using PRCs introduces additional measurements and estimates that contribute to the uncertainty of CPE estimates. Often in situ, PRC‐based estimates of CPE are validated by comparing equilibrium‐estimated C free values with synonymous ex situ deployments where equilibrium had been confirmed (Gschwend et al 2011; Fernandez et al 2014; Apell and Gschwend 2016; Schmidt et al 2017). In general, the estimated C free values when equilibrium had been achieved or when it had been modeled using PRC data agreed within a factor of 2.…”
Section: Introductionmentioning
confidence: 99%